The effectiveness of the outing class method in history learning: A quantitative and bibliometric approach - Septiyaningsih, Imada Cahya; Setiawan, Risky; Aditia, Dimas (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
History learning has great potential in building students' historical awareness. However, most students still find it difficult to understand historical concepts, especially those related to past events and cannot be experienced directly. This research evaluates how effective the outing class method is in comparison to traditional methods for enhancing history learning outcomes. Utilizing a quasi-experimental design that incorporates pre-tests and post-tests within the control group, a quantitative approach is employed in this study. A sample comprising two classes X at SMA N 1 Dukuhwaru was determined using a random sampling technique. The experimental group engaged with the outing class method, whereas the control group followed the conventional approach. Findings from the paired sample t-test indicated a notable improvement in the experimental group (p < 0.05), with the average post-test score rising from 71.3 to 89.0, while the control group only increased from 66.7 to 69.8. Bibliometric analysis also shows a lack of similar research in the historical context. The study confirms that Outing Classes can significantly improve student learning outcomes, as well as recommending broader implementation in the history curriculum for a more contextual and interactive learning experience.